GLOBLIZATION TO GLOCALIZATION OF MNFEs IN INDIA WITH SPECIAL REFERENCE TOFOOD ENTERPRISES IN LUCKNOW (INTERNATIONAL JOURNAL OF RESEARCH IN EDUCATION METHODOLOGY, 2014)
The concept of Glocalization is derived from that of globalization and localization and signifies that companies should not only think globally but also act locally while addressing business functionalities including branding, marketing, advertising and product promotion. Food industry, of India and World is witnessing unprecedented increase in the number of multinational enterprises. These multinational enterprises, when deciding to expand their operations to a new country, have to make a choice between following uniform business strategies as in their home country or modify their strategies to suit the host country socio-economic and political environment. Recently, many multinational food giants have successfully penetrated into emerging markets due to their product or service quality but there are cases where companies have failed to earn profits due to lack of Glocalization strategies. This paper focuses on multinational food Enterprises (MNFEs) and identifies suitable Glocalized strategies in marketing, product development, advertisement etc. establishing themselves and gaining market share in a diverse country like India.